Calculation Procedure for Dynamic Condition of Ion Composition in Cell Walls Altered by Proton Fluxes - Idam Arif (Institut Teknologi Bandung, 2011)
The calculation procedure has been developed to determine the dynamic condition of the ion composition in cell walls during proton extrusion, known as the Weak Acid Donnan Manning (WADM) model for fluxes. In this model, the walls of plant cells are considered as a system containing weak acid polymers where the interaction of ions obeys the Manning condensation theory and the Donnan theory. When protons are transported across the walls during proton fluxes, the transported proton will interact with the wall ions and alter the ion composition. This depends on the wall parameters such as the concentration of ionisable sites, the pK of the wall weak acid, and the wall linear charge density parameter. When the linear charge density parameter is still higher than the reciprocal of the highest valence of the involve cations, the transported protons during proton fluxes will decrease the wall pH, alter the ion composition in the wall Donnan free space and water free space, and release the condensed cations. Therefore some of the proton fluxes are represented by the flux of the condensed cations outside the walls. However when the linear charge density parameter is less than the reciprocal of the highest valence of the involve cations, there is no condensed cations in the walls so that the transported protons only alter the ion composition in the wall Donnan free space and water free space.